Shielding protection adhesive tape for semiconductor integrated circuit packaging and preparation method thereof

By combining modified nano-silica and modified acrylate copolymer with polyimide substrate, the problems of shielding reliability and weather resistance of shielding protective tape in semiconductor packaging process are solved, forming a dense coating to ensure the stability and shielding performance of the tape in high temperature, ultraviolet and chemical reagent environments, meeting the packaging requirements of high precision and high reliability.

CN120818312AInactive Publication Date: 2025-10-21SUZHOU K-HIRAGAWA ELECTRONIC TECHNOLOGY CO LTD

Patent Information

Application Number
CN202511334053.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-18
Publication Date
2025-10-21
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing masking and protective tapes have problems such as poor masking reliability, weak weather resistance and aging resistance, unbalanced mechanical properties and low mass production consistency in the semiconductor integrated circuit packaging process. In addition, the lack of precise control over the manufacturing process leads to problems such as coating peeling, residual adhesive and performance degradation.

Method used

By combining modified nano-silica, modified acrylate copolymer and polyimide substrate in a specific ratio, and through precise raw material pretreatment and coating preparation process, a strong and dense coating is formed. Combined with antioxidants, UV absorbers and flame retardants, the stability and masking performance of the tape are ensured in high temperature, UV and chemical reagent environments.

Benefits of technology

It achieves coating-free curing and subsequent peeling processes, possesses excellent shielding performance and long-term stability, combines high strength and flexibility, meets the high precision and high reliability requirements of semiconductor packaging, and has good mass production consistency.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a shielding protection adhesive tape for semiconductor integrated circuit packaging and a preparation method thereof, and relates to the technical field of semiconductor integrated circuit packaging. The shielding protective adhesive tape for packaging the semiconductor integrated circuit is prepared by taking polyimide as a base material and coating a coating, and the coating comprises the following raw materials in parts by weight: 3-5 parts of modified nano silicon dioxide, 30-40 parts of N, N-dimethylformamide, 1-3 parts of a curing agent and 1-3 parts of a curing agent. The invention discloses a high-temperature-resistant epoxy resin coating which is prepared from the following components in parts by weight: 25-30 parts of N, N-dimethylformamide, 25-30 parts of a modified acrylate copolymer, 17-26 parts of ethyl acetate, 12-15 parts of epoxy resin, 1-2 parts of a silane coupling agent KH-550, 0.5-1 part of an antioxidant 1010, 0.3-0.8 part of an ultraviolet absorbent UV-327, 1-2 parts of carboxyl-terminated nitrile rubber, 2-4 parts of decabromodiphenyl ether, 0.1-0.3 part of an organic siloxane defoaming agent, 0.2-0.5 part of an acrylate flatting agent and 10-11 parts of diaminodiphenyl sulfone. The adhesive tape contains the modified nano silicon dioxide, the modified acrylate copolymer and other components, so that the performance of the adhesive tape is guaranteed; pretreatment is meticulous, preparation steps are standard, and mass production is easy; a finished product can be effectively shielded, and the packaging yield and the product stability can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of semiconductor integrated circuit packaging, in particular to a masking protective tape for semiconductor integrated circuit packaging and a preparation method thereof. Background Art

[0002] Amidst the rapid growth of the semiconductor integrated circuit industry, the packaging process, a critical step in ensuring chip performance, stability, and longevity, places stringent demands on the performance of protective masking materials. Currently, during the semiconductor integrated circuit packaging process, non-packaged chip areas must be precisely masked with protective masking tape to prevent material adhesion, mechanical scratches, or chemical corrosion during soldering, coating, and gluing. Furthermore, these materials must withstand the complex working conditions of high temperatures, UV radiation, and chemical reagents encountered during the packaging process.

[0003] However, existing masking protective tapes generally have performance shortcomings in many aspects: First, some products use traditional resins as the coating matrix, which has weak bonding with the polyimide substrate. During high-temperature curing or subsequent stripping, problems such as coating peeling and residual adhesive are prone to occur, resulting in a decrease in chip packaging yield; Second, commonly used fillers such as ordinary nano-silica have poor dispersibility and are prone to agglomeration in the coating, which not only affects the flatness and masking accuracy of the tape, but also reduces its mechanical strength and anti-aging properties; Third, due to the particularity of the semiconductor packaging environment, the existing tapes are difficult to balance the anti-UV aging, chemical corrosion resistance and flame retardancy, and are prone to performance degradation after long-term use, and cannot meet the high-precision and high-reliability packaging requirements.

[0004] Furthermore, existing tape manufacturing processes lack key raw material pretreatment procedures or have ambiguous parameters. For example, carboxyl-terminated nitrile rubber is not rigorously dried and diaminodiphenyl sulfone particle size is poorly controlled. This leads to poor raw material compatibility and uneven cross-linking reactions, further impacting the stability of the finished product. Furthermore, the dispersion and curing parameters in the coating preparation process lack precise control standards, leading to batch-to-batch performance variations and hindering large-scale mass production. Therefore, developing a masking tape for semiconductor integrated circuit packaging with a scientific raw material ratio, a controllable preparation process, and excellent overall performance has become the key to addressing current industry pain points. Summary of the Invention

[0005] In response to the shortcomings of the existing technology, the present invention provides a masking protective tape for semiconductor integrated circuit packaging and a preparation method thereof, which solves the problems of poor masking reliability, weak weather resistance and aging resistance, unbalanced mechanical properties, and low mass production consistency of traditional tapes.

[0006] To achieve the above objectives, the present invention is implemented through the following technical solutions: The invention relates to a masking protective tape for semiconductor integrated circuit packaging. The masking protective tape is prepared by coating a polyimide as a base material. The coating comprises the following raw materials in parts by weight: 3-5 parts of modified nano-silica, 30-40 parts of N,N-dimethylformamide, 25-30 parts of modified acrylate copolymer, 17-26 parts of ethyl acetate, 12-15 parts of epoxy resin, 1-2 parts of silane coupling agent KH-550, 0.5-1 part of antioxidant 1010, 0.3-0.8 part of ultraviolet absorber UV-327, 1-2 parts of carboxyl-terminated nitrile rubber, 2-4 parts of decabromodiphenyl ether, 0.1-0.3 parts of organosiloxane defoaming agent, 0.2-0.5 parts of acrylate leveling agent, and 10-11 parts of diaminodiphenyl sulfone.

[0007] Furthermore, the carboxyl-terminated nitrile rubber has a number average molecular weight of 3000-5000 and an acrylonitrile content of 28%-32%. It needs to be dried before use by placing the carboxyl-terminated nitrile rubber in a vacuum drying oven at 70-80°C and a vacuum degree of -0.08 to -0.09 MPa for 3-4 hours to ensure that the moisture content drops below 0.5%. After drying, it is sealed and stored. Vacuum drying can effectively remove moisture, prevent moisture from forming bubbles during coating curing, and avoid moisture affecting compatibility with the resin, ensuring the density of the coating and reducing the risk of chemical reagent penetration during packaging.

[0008] Furthermore, the diaminodiphenyl sulfone needs to be ground and screened using a planetary ball mill. The grinding medium is agate balls, the ball-to-material ratio is 8:1, the grinding speed is 350 r / min, and the grinding time is 2.5 hours. After grinding, the diaminodiphenyl sulfone is screened through a 400-mesh sieve, and the undersize is collected as the diaminodiphenyl sulfone for final use. The screened diaminodiphenyl sulfone needs to be stored in a dry environment with a relative humidity of ≤40% to avoid uneven cross-linking reaction caused by particle agglomeration. Grinding with agate balls can avoid contamination by metal impurities, and screening with 400-mesh sieving controls the particle size, preventing large particles from causing uneven distribution of cross-linking points and avoiding localized weak coating performance. Dry storage inhibits particle agglomeration, ensuring uniform dispersion during reaction with epoxy resin, and improving the cross-linking density and structural stability of the coating.

[0009] Furthermore, the modified nano-silica is prepared in the following steps: A1. Add 15% hydrochloric acid solution by mass to nano-silicon dioxide, heat to 60-70°C, stir at 250-300 r / min and react for 4-5 hours; filter after reaction, wash with deionized water until neutral, add 8% sodium hydroxide solution by mass, heat to 50-60°C, stir and react for 3-4 hours; filter again and wash repeatedly with deionized water until neutral, add deionized water, ultrasonically disperse at 500W power for 30-40 minutes, add 30% by mass of sodium hydroxide solution. The reaction mixture was stirred at 40-50 ° C for 2-3 hours, and finally vacuum dried at 90-100 ° C for 6-7 hours to obtain the first modified nano-silica; hydrochloric acid and sodium hydroxide acid-base treatment can remove impurities on the surface of nano-silica, etch the surface to form a porous structure, and increase active sites; 500W ultrasonic dispersion was used to break the initial agglomeration; hydrogen peroxide oxidized to introduce hydroxyl groups, providing a reaction basis for subsequent organic grafting, while improving its dispersibility in the coating, avoiding coating defects caused by agglomeration of original nanoparticles.

[0010] A2. Dissolve acrylamide and methyl methacrylate in an ethanol-water solution with a volume ratio of 3:1, then add azobisisobutyronitrile and stir to dissolve to form a monomer solution; add the first modified nano-silica to the monomer solution, ultrasonically disperse for 20-30 minutes, heat to 70-80°C, introduce nitrogen protection, and stir at 200-250r / min for 6-8 hours; after the reaction, centrifuge for 15 minutes, wash with ethanol three times, and vacuum dry at 80-90°C for 5-6 hours to obtain the second modified nano-silica; the ethanol-water solution provides a compatible environment for the monomer and nanoparticles, and azobisisobutyronitrile initiates polymerization at 70-80°C; acrylamide and methyl methacrylate are grafted on the surface of the nano-silica, introducing organic chain segments to improve its compatibility with the modified acrylate copolymer, avoid stratification of inorganic particles and organic resin, and improve the overall uniformity of the coating.

[0011] A3. Dissolve hexamethylene diisocyanate and ethyl orthosilicate in ethyl acetate, then add dibutyltin dilaurate and stir for 20-30 minutes to form a crosslinker solution. Add the second modified nano-silica to the crosslinker solution, heat to 50-60°C, and stir at 180-220 rpm for 4-5 hours. After the reaction, filter and wash three times with ethyl acetate. Vacuum cure at 100-110°C for 3-4 hours to obtain modified nano-silica. Dibutyltin dilaurate catalyzes the formation of a crosslinked structure between hexamethylene diisocyanate and ethyl orthosilicate. The reaction at 50-60°C promotes the binding of the crosslinker to the surface groups of the nanoparticles. Vacuum cure at 100-110°C strengthens the crosslinking, constructs a three-dimensional network structure, and enhances the nano-silica's effect on the mechanical strength and thermal stability of the coating, making the tape less susceptible to deformation during high-temperature packaging.

[0012] Furthermore, the usage ratio of nano-silica, hydrochloric acid solution, sodium hydroxide solution, deionized water and hydrogen peroxide in A1 is 350-400 g: 900-1000 ml: 800-900 ml: 500-600 ml: 5-8 ml.

[0013] Furthermore, the usage ratio of acrylamide, methyl methacrylate, ethanol-water solution, azobisisobutyronitrile, and first modified nano-silica in A2 is 15-20 g: 12-16 g: 400-500 ml: 0.8-1.2 g: 280-320 g.

[0014] Furthermore, the usage ratio of hexamethylene diisocyanate, ethyl orthosilicate, ethyl acetate, dibutyltin dilaurate, and the second modified nano-silica in A3 is 8-12g: 10-14g: 200-250ml: 0.3-0.5g: 200-240g.

[0015] Furthermore, the modified acrylate copolymer is specifically prepared in the following steps: B1. Add 160-190 ml of toluene to a four-necked flask, raise the temperature to 85-90°C, and introduce nitrogen protection; dissolve ethyl acrylate, butyl methacrylate, and 4-hydroxyphenyl trifluoromethylacrylate in toluene to form a monomer solution, and dissolve benzoyl peroxide in toluene to form an initiator solution; first dropwise add 1 / 4 of the monomer solution and 1 / 2 of the initiator solution to the four-necked flask for 30-40 minutes, continue the constant temperature reaction for 1-1.5 hours, then add the remaining monomer solution dropwise in three equal portions, with an interval of 1 hour between each addition, and add 1 / 4 of the total amount of initiator solution after each addition. After the dripping is completed, the temperature is raised to 95-100°C and the reaction is continued for 4-5 hours; after the reaction, it is cooled to room temperature, petroleum ether is added for precipitation, the polymer is collected by filtration, washed with petroleum ether three times, and vacuum dried at 75-85°C for 6-7 hours to obtain the first modified acrylate copolymer; benzoyl peroxide is added step by step to control the polymerization rate to avoid local overheating causing molecular chain breakage; trifluoromethylacrylate-4-hydroxyphenyl ester introduces fluorine-containing groups and hydroxyl groups, the fluorine-containing groups improve the chemical corrosion resistance of the coating, and the hydroxyl groups provide sites for subsequent cross-linking. Petroleum ether precipitation and vacuum drying are used to remove impurities and ensure the purity of the copolymer.

[0016] B2. Take nano zinc oxide and add ethanol, ultrasonically disperse at 400W power for 25-35 minutes, add silane coupling agent KH-570, and stir at 50-60℃ for 2-3 hours to obtain nano zinc oxide dispersion; dissolve the first modified acrylate copolymer in butyl acetate, heat to 70-80℃, stir at 250-300r / min until completely dissolved, slowly add nano zinc oxide dispersion, stir with the assistance of ultrasound at 400W power for 40-50 minutes, then add polyethylene glycol, continue stirring for 2-3 hours, cool to room temperature to obtain the second modified acrylate copolymer; polyethylene glycol adjusts the fluidity of the system, nano zinc oxide improves the coating's anti-ultraviolet aging performance, and at the same time enhances the mechanical strength, avoiding the problem of insufficient anti-ultraviolet ability when the copolymer is used alone.

[0017] B3. Dissolve bisphenol A epoxy acrylate and di-tert-butyl peroxide in ethyl acetate and stir for 30-40 minutes to form a crosslinking system. Add the second modified acrylate copolymer dispersion to the crosslinking system, heat to 85-95°C, and stir at 200-250 rpm for 5-6 hours. Apply the reaction solution to a polyimide substrate with a wet film thickness of 25-35 μm. Pre-bake at 90-100°C for 1-2 hours, then heat to 130-140°C and post-cure for 4-5 hours to obtain the modified acrylate copolymer. Di-tert-butyl peroxide initiates crosslinking between the bisphenol A epoxy acrylate and the copolymer at 85-95°C. A stepwise temperature curing process first removes the solvent to prevent bubbling, followed by high temperature to strengthen the crosslinking structure. A wet film thickness of 25-35 μm controls the final coating thickness, forming a high-strength, high-density copolymer structure that improves adhesion to the polyimide substrate and prevents coating shedding during encapsulation.

[0018] Furthermore, the ratio of ethyl acrylate, butyl methacrylate, 4-hydroxyphenyl trifluoromethylacrylate, and toluene in the monomer solution of B1 is 40-45 g: 25-30 g: 15-20 g: 70-90 ml; the ratio of benzoyl peroxide and toluene in the initiator solution is 1.5-2 g: 70-90 ml; and 160-190 ml of toluene is added to the four-necked flask as the reaction solvent.

[0019] Furthermore, the usage ratio of nano zinc oxide, ethanol, and silane coupling agent KH-570 in the nano zinc oxide dispersion in B2 is 10-15g:100-120ml:3-5ml; the usage ratio of the first modified acrylate copolymer, butyl acetate, and polyethylene glycol is 100-120g:200-240ml:2-3g.

[0020] Furthermore, the usage ratio of bisphenol A epoxy acrylate, di-tert-butyl peroxide, and ethyl acetate in the cross-linking system in B3 is 18-22 g: 1.2-1.8 g: 80-100 ml.

[0021] A method for preparing a masking protective tape for semiconductor integrated circuit packaging, comprising the following steps: S1. Dissolving the modified nano-silica in N,N-dimethylformamide and ultrasonically dispersing for 30 minutes to prepare a modified nano-silica dispersion; dissolving the modified acrylate copolymer in ethyl acetate and stirring until completely dissolved to prepare a modified acrylate copolymer solution; S2. Add N,N-dimethylformamide to the reactor, stir at 300-400 r / min and raise the temperature to 40-45°C, add the modified acrylate copolymer solution, and stir for 15-20 minutes until uniform; then add the epoxy resin, raise the temperature to 50-55°C, increase the speed to 500-600 r / min, and stir for 30-40 minutes to form a mixed resin system, which can enhance the dissolution and dispersion efficiency of the epoxy resin, avoid uneven cross-linking caused by agglomeration of the epoxy resin, form a uniform resin matrix, and provide a stable system for the subsequent addition of functional additives; S3. First add silane coupling agent KH-550 to the mixed resin and stir for 10-15 minutes, then add modified nano-silica dispersion, perform 500W ultrasonic dispersion for 30-40 minutes and maintain stirring at 400-500r / min; add antioxidant 1010, UV absorber UV-327, carboxyl-terminated nitrile rubber, and decabromodiphenyl ether in sequence, stirring for 20-25 minutes each time; finally add organosiloxane defoamer and acrylate leveling agent, stir at 200-300r / min for 15-20 minutes; add functional additives in batches and stir thoroughly to avoid mutual interference between additives, ensuring that antioxidant, anti-UV, flame retardant and other functions are evenly imparted to the coating; defoamer and leveling agent improve the appearance of the coating and reduce bubbles and orange peel defects; S4. Cool the reactor to 30-35°C, add diaminodiphenyl sulfone and stir for 25-30 minutes to avoid premature crosslinking caused by high temperature; measure the viscosity and adjust it to 8000-12000 mPa·s, adjust the solid content to 48%-52%, filter the prepared coating through three layers of filter cloth with 10μm, 5μm and 2μm diameters, transfer the filtrate into a sealed tank, age at 25-30°C in the dark for 8-10 hours, and stir at 100-150 r / min for 5-10 minutes every 2 hours to prevent precipitation, thereby preparing the coating; three-layer filtration removes impurities and agglomerated particles, ageing in the dark promotes slow fusion of components, and stirring prevents precipitation to ensure uniformity of the coating; S5. Cut the polyimide substrate into the required size, wipe it with ethanol to remove dust, and then vacuum dry it at 120-130℃ for 4-5h, then cool it to 30-40℃. Wipe it with ethanol and vacuum dry it to remove impurities and moisture on the surface of the substrate to prevent poor bonding between the coating and the substrate; send it to the coating machine, add the coating to the coating machine storage tank, control the wet film thickness to 30-35μm, and apply it to one side of the substrate at a speed of 0.8-1m / min to avoid orange peel and missing coating; ensure that the coating thickness is uniform and consistent, avoid local excessive thickness resulting in incomplete curing or excessive thinness resulting in shielding failure, and ensure shielding accuracy; S6. The coated substrate is pre-baked at 90-100°C for 2-3 hours to remove the solvent to prevent rapid volatilization of the solvent which may cause bubbling or cracking of the coating; then the substrate is cured at 120-130°C for 3.5-4.5 hours to promote full cross-linking of the coating and form a dense protective layer; after curing, the semi-finished product is cooled to room temperature via a 25°C cooling roller to avoid deformation of the coating at high temperature and ensure the dimensional stability of the tape, thereby giving the tape excellent masking and weather resistance properties to obtain a masking protective tape for semiconductor integrated circuit packaging.

[0022] Furthermore, the solid content in S4 is adjusted. If the solid content is too high, N,N-dimethylformamide is added for adjustment. If the solid content is too low, the solid content is stirred and volatilized at 40°C.

[0023] The present invention provides a masking protective tape for semiconductor integrated circuit packaging and a preparation method thereof, which has the following beneficial effects: 1. The present invention utilizes a specific ratio of modified nano-silica and modified acrylate copolymer to work synergistically. After the modified nano-silica is treated with hydrochloric acid and sodium hydroxide and grafted with acrylamide and hexamethylene diisocyanate, the surface active groups increase, forming strong chemical bonds with the hydroxyl and ester groups in the modified acrylate copolymer. Simultaneously, the modified acrylate copolymer is modified with nano-zinc oxide and cross-linked with bisphenol A epoxy acrylate, making the molecular chain structure more stable and enhancing its interfacial compatibility with the polyimide substrate. Under the epoxy resin cross-linking system, the two, combined with the bridging effect of the silane coupling agent KH-550, can form a dense, highly adhesive, non-porous coating on the surface of the polyimide substrate, effectively preventing welding fluids, coating materials, etc. from penetrating into the shielded area during the packaging process. Furthermore, during high-temperature curing and subsequent stripping, there is no coating shedding or adhesive residue, ensuring precise shielding and surface cleanliness for chip packaging.

[0024] 2. The antioxidant 1010 and UV absorber UV-327 in the coating system form a synergistic protective mechanism. Antioxidant 1010 can capture free radicals generated in the high-temperature environment of the encapsulation process, inhibiting the oxidative degradation of the coating's molecular chains. The UV absorber UV-327, which has been dissolved in ethanol and pre-treated with ultrasonic dispersion, is evenly dispersed and can effectively absorb UV light in the encapsulation workshop, preventing the coating from yellowing and brittleness due to UV exposure. At the same time, the addition of modified nano-silica enhances the thermal stability of the coating, while the carboxyl-terminated nitrile rubber improves the coating's toughness. This allows the tape to withstand the complex working conditions of the semiconductor encapsulation process, such as pre-baking and curing temperatures of 90-130°C, UV exposure, and chemical reagent exposure. It maintains excellent shielding properties and structural integrity after long-term use, extending the tape's service life while ensuring the long-term stability of the chip after encapsulation.

[0025] 3. The flame retardant decabromodiphenyl ether in the formula not only imparts excellent flame retardancy to the tape, but its particles also provide a certain degree of reinforcement when evenly dispersed within the coating. After undergoing multi-step modification, modified nano-silica exhibits no agglomeration in the coating and can evenly fill the gaps between resin molecules, significantly enhancing the coating's tensile strength and hardness. The carboxyl-terminated nitrile rubber exhibits excellent compatibility with the resin system after vacuum drying, and its flexible molecular chains form an elastic network within the coating, mitigating damage to the coating from external mechanical impact. The synergistic effect of these three factors gives the tape both high mechanical strength and excellent flexibility. It is not susceptible to breakage due to stretching or bending during the encapsulation process, and is also resistant to minor mechanical scratches, ensuring that the shielded area remains effectively protected.

[0026] 4. This invention establishes precise parameter ranges for each step in the pretreatment of key raw materials and coating preparation, and sets a nitrogen atmosphere and precise temperature range for coating curing. Furthermore, three layers of filtration are used to remove coating impurities, and aging at 25-30°C in the dark ensures full integration of the components. Viscosity and solid content adjustment standards are also clearly defined to effectively avoid performance variations between batches. This standardized process reduces the difficulty of production operations and can stably produce masking tapes with consistent performance, meeting the large-scale, high-quality production needs of the semiconductor integrated circuit packaging industry. DETAILED DESCRIPTION

[0027] The following is a clear and complete description of the technical solutions in the embodiments of the present invention. Obviously, the embodiments described are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making any creative efforts are within the scope of protection of the present invention.

[0028] Example 1: Preparation of a masking protective tape for semiconductor integrated circuit packaging. The specific preparation steps are as follows: S1, dissolving 3 parts of nano-silica in 8 parts of N,N-dimethylformamide, and ultrasonically dispersing for 30 minutes to prepare a nano-silica dispersion; taking 25 parts of acrylate copolymer and dissolving it in 17 parts of ethyl acetate, and stirring until completely dissolved to prepare an acrylate copolymer solution; S2. Add 22 parts of N,N-dimethylformamide to the reactor, stir at 300 r / min and heat to 40°C, add the acrylate copolymer solution, and stir for 15 minutes until uniform; then add 15 parts of epoxy resin, heat to 50°C, increase the speed to 500 r / min, and stir for 30 minutes to form a mixed resin system; S3. First, add 1 part of silane coupling agent KH-550 to the mixed resin and stir for 10 minutes. Then add nano-silica dispersion, ultrasonically disperse at 500W for 30 minutes and maintain stirring at 400r / min. Then, add 0.5 parts of antioxidant 1010, 0.3 parts of UV absorber UV-327, 1 part of carboxyl-terminated nitrile rubber, and 2 parts of decabromodiphenyl ether in sequence, stirring for 20 minutes each time. Finally, add 0.1 parts of organosiloxane defoamer and 0.2 parts of acrylate leveling agent, and stir at 200r / min for 15 minutes. S4. The reaction kettle was cooled to 30°C, 10 parts of diaminodiphenyl sulfone was added and stirred for 25 minutes, the viscosity was measured and adjusted to 8000 mPa·s, the solid content was adjusted to 48%, and the prepared coating was filtered through three layers of filter cloth with 10 μm, 5 μm, and 2 μm. The filtrate was transferred to a sealed tank and aged at 25°C in the dark for 8 hours. The mixture was stirred at 100 r / min for 5 minutes every 2 hours to prevent precipitation, thereby obtaining a coating; S5. Cut the polyimide substrate into the required size, wipe it with ethanol to remove dust, dry it in vacuum at 120°C for 4 hours, and then cool it to 30°C. Send it to the coating machine, add the coating into the coating machine storage tank, control the wet film thickness to 30μm, and apply it on one side of the substrate at a speed of 0.8m / min to avoid orange peel and missing coating on the coating; S6. The coated substrate is pre-baked at 90°C for 2 hours to remove the solvent, and then cured at 120°C for 3.5 hours to cross-link the coating into a dense layer; after curing, the semi-finished product is cooled to room temperature via a 25°C cooling roller to obtain a masking protective tape for semiconductor integrated circuit packaging.

[0029] Example 2: Preparation of a masking protective tape for semiconductor integrated circuit packaging. The specific preparation steps are as follows: S1, dissolving 5 parts of nano-silica in 10 parts of N,N-dimethylformamide, and ultrasonically dispersing for 30 minutes to prepare a nano-silica dispersion; taking 30 parts of an acrylate copolymer and dissolving it in 26 parts of ethyl acetate, and stirring until completely dissolved to prepare an acrylate copolymer solution; S2. Add 30 parts of N,N-dimethylformamide to the reactor, stir at 400 r / min and raise the temperature to 45°C, add the acrylate copolymer solution, and stir for 20 minutes until uniform; then add 15 parts of epoxy resin, raise the temperature to 55°C, increase the speed to 600 r / min, and stir for 40 minutes to form a mixed resin system; S3. First, add 2 parts of silane coupling agent KH-550 to the mixed resin and stir for 15 minutes. Then add nano-silica dispersion, ultrasonically disperse at 500W for 40 minutes and maintain stirring at 500r / min. Then, add 1 part of antioxidant 1010, 0.8 parts of ultraviolet absorber UV-327, 2 parts of carboxyl-terminated nitrile rubber, and 4 parts of decabromodiphenyl ether in sequence, stirring for 25 minutes each time. Finally, add 0.3 parts of organosiloxane defoamer and 0.5 parts of acrylate leveling agent, and stir at 300r / min for 20 minutes. S4. The reaction kettle was cooled to 35°C, 11 parts of diaminodiphenyl sulfone was added and stirred for 30 minutes, the viscosity was measured and adjusted to 12000 mPa·s, the solid content was adjusted to 52%, and the prepared coating was filtered through three layers of filter cloth with 10 μm, 5 μm, and 2 μm. The filtrate was transferred to a sealed tank and aged at 30°C in the dark for 10 hours. The mixture was stirred at 150 r / min for 10 minutes every 2 hours to prevent precipitation, thereby obtaining a coating; S5. Cut the polyimide substrate into the required size, wipe it with ethanol to remove dust, dry it in vacuum at 130°C for 5 hours, and then cool it to 40°C. Send it to the coating machine, add the coating into the coating machine storage tank, control the wet film thickness to 35μm, and apply it to one side of the substrate at a speed of 1m / min to avoid orange peel and missing coating on the coating; S6. The coated substrate is pre-baked at 100°C for 3 hours to remove the solvent, and then cured at 130°C for 4.5 hours to cross-link the coating into a dense layer; after curing, the semi-finished product is cooled to room temperature via a 25°C cooling roller to obtain a masking protective tape for semiconductor integrated circuit packaging.

[0030] Example 3: Preparation of a masking protective tape for semiconductor integrated circuit packaging. The specific preparation steps are as follows: S1, dissolving 4 parts of nano-silica in 9 parts of N,N-dimethylformamide, and ultrasonically dispersing for 30 minutes to prepare a nano-silica dispersion; taking 27 parts of acrylate copolymer and dissolving it in 22 parts of ethyl acetate, and stirring until completely dissolved to prepare an acrylate copolymer solution; S2. Add 26 parts of N,N-dimethylformamide to the reactor, stir at 350 r / min and raise the temperature to 42°C, add the acrylate copolymer solution, and stir for 17 minutes until uniform; then add 13 parts of epoxy resin, raise the temperature to 52°C, increase the speed to 550 r / min, and stir for 35 minutes to form a mixed resin system; S3. First, add 1.5 parts of silane coupling agent KH-550 to the mixed resin and stir for 12 minutes. Then add nano-silica dispersion, ultrasonically disperse at 500W for 35 minutes and maintain stirring at 450r / min. Then, add 0.7 parts of antioxidant 1010, 0.5 parts of UV absorber UV-327, 1 part of carboxyl-terminated nitrile rubber, and 3 parts of decabromodiphenyl ether in sequence, stirring for 22 minutes each time. Finally, add 0.2 parts of organosiloxane defoamer and 0.3 parts of acrylate leveling agent, and stir at 250r / min for 17 minutes. S4. The reactor was cooled to 32°C, 10 parts of diaminodiphenyl sulfone was added and stirred for 27 minutes, the viscosity was measured and adjusted to 10,000 mPa·s, the solid content was adjusted to 50%, and the prepared coating was filtered through three layers of filter cloth with 10 μm, 5 μm, and 2 μm. The filtrate was transferred to a sealed tank and aged at 27°C in the dark for 9 hours. The mixture was stirred at 120 r / min for 8 minutes every 2 hours to prevent precipitation, thereby obtaining a coating; S5. Cut the polyimide substrate into the required size, wipe it with ethanol to remove dust, dry it in vacuum at 125°C for 4.5 hours, and then cool it to 35°C. Send it to the coating machine, add the coating into the coating machine storage tank, control the wet film thickness to 32μm, and apply it to one side of the substrate at a speed of 0.9m / min to avoid orange peel and missing coating on the coating; S6. The coated substrate is pre-baked at 95°C for 2.5 hours to remove the solvent, and then cured at 125°C for 4 hours to cross-link the coating into a dense layer; after curing, the semi-finished product is cooled to room temperature via a 25°C cooling roller to obtain a masking protective tape for semiconductor integrated circuit packaging.

[0031] Example 4: Preparation of modified nano-silica. The specific preparation steps are as follows: A1. Take 350g of nano-silica and add 900ml of 15% hydrochloric acid solution, heat to 60℃, and stir at 250r / min for 4h; after the reaction, filter, wash with deionized water until neutral, add 800ml of 8% sodium hydroxide solution, heat to 50℃, and stir for 3h; filter again and wash repeatedly with deionized water until neutral, add 500ml of deionized water, ultrasonically disperse at 500W power for 30min, add 5ml of 30% hydrogen peroxide, stir at 40℃ for 2h, and finally vacuum dry at 90℃ for 6h to obtain the first modified nano-silica; A2. Dissolve 15 g of acrylamide and 12 g of methyl methacrylate in 400 ml of an ethanol-water solution with a volume ratio of 3:1, then add 0.8 g of azobisisobutyronitrile and stir to dissolve to form a monomer solution; add 280 g of the first modified nano-silica to the monomer solution, ultrasonically disperse for 20 min, heat to 70°C, introduce nitrogen protection, and stir at 200 r / min for 6 h; after the reaction, centrifuge for 15 min, wash with ethanol three times, and vacuum dry at 80°C for 5 h to obtain the second modified nano-silica; A3. Dissolve 8 g of hexamethylene diisocyanate and 10 g of ethyl orthosilicate in 200 ml of ethyl acetate, then add 0.3 g of dibutyltin dilaurate and stir for 20 min to form a crosslinker solution; add 200 g of the second modified nano-silica to the crosslinker solution, heat to 50 ° C, and stir at 180 r / min for 4 h; after the reaction, filter, wash with ethyl acetate 3 times, and vacuum cure at 100 ° C for 3 h to obtain modified nano-silica.

[0032] Example 5, preparation of modified nano-silica, the specific preparation steps are as follows: A1. Take 400g of nano-silica, add 1000ml of 15% hydrochloric acid solution by mass, heat to 70°C, and stir at 300r / min for 5h; after the reaction, filter, wash with deionized water until neutral, add 900ml of 8% sodium hydroxide solution by mass, heat to 60°C, and stir for 4h; filter again and wash repeatedly with deionized water until neutral, add 600ml of deionized water, ultrasonically disperse at 500W power for 40min, add 8ml of 30% hydrogen peroxide by mass, stir at 50°C for 3h, and finally vacuum dry at 100°C for 7h to obtain the first modified nano-silica; A2. Dissolve 20 g of acrylamide and 16 g of methyl methacrylate in 500 ml of an ethanol-water solution with a volume ratio of 3:1, then add 1.2 g of azobisisobutyronitrile and stir to dissolve to form a monomer solution; add 320 g of the first modified nano-silica to the monomer solution, ultrasonically disperse for 30 min, heat to 80°C, introduce nitrogen protection, and stir at 250 r / min for 8 h; after the reaction, centrifuge for 15 min, wash with ethanol three times, and vacuum dry at 90°C for 6 h to obtain the second modified nano-silica; A3. Dissolve 12 g of hexamethylene diisocyanate and 14 g of ethyl orthosilicate in 250 ml of ethyl acetate, add 0.5 g of dibutyltin dilaurate, and stir for 30 min to form a crosslinker solution; add 240 g of the second modified nano-silica to the crosslinker solution, heat to 60 ° C, and stir at 220 r / min for 5 h; after the reaction, filter, wash with ethyl acetate 3 times, and vacuum cure at 110 ° C for 4 h to obtain modified nano-silica.

[0033] Example 6: Preparation of modified acrylate copolymer. The specific preparation steps are as follows: B1. Add 160 ml of toluene to a four-necked flask, raise the temperature to 85° C., introduce nitrogen protection, then dissolve 40 g of ethyl acrylate, 25 g of butyl methacrylate, and 15 g of 4-hydroxyphenyl trifluoromethylacrylate in 70 ml of toluene to form a monomer solution, and dissolve 1.5 g of benzoyl peroxide in 70 ml of toluene to form an initiator solution; first, add 1 / 4 of the monomer solution and 1 / 2 of the initiator solution dropwise to the four-necked flask for 30 min, continue the constant temperature reaction for 1 h, then add the remaining monomer solution dropwise in three equal parts, each with an interval of 1 h, and add 1 / 4 of the total initiator solution after each addition. After the addition is complete, raise the temperature to 95° C. and continue the reaction for 4 h; after the reaction, cool to room temperature, add petroleum ether for precipitation, collect the polymer by filtration, wash with petroleum ether three times, and vacuum dry at 75° C. for 6 h to obtain a first modified acrylate copolymer; B2, take 10g of nano zinc oxide, add 100ml of ethanol, ultrasonically disperse for 25min at 400W power, add 3ml of silane coupling agent KH-570, and stir at 50°C for 2h to obtain a nano zinc oxide dispersion; dissolve 100g of the first modified acrylate copolymer in 200ml of butyl acetate, heat to 70°C, stir at 250r / min until completely dissolved, slowly add the nano zinc oxide dispersion, stir with 400W power ultrasound for 40min, then add 2g of polyethylene glycol, continue stirring for 2h, and cool to room temperature to obtain a second modified acrylate copolymer; B3. Dissolve 18 g of bisphenol A epoxy acrylate and 1.2 g of di-tert-butyl peroxide in 80 ml of ethyl acetate and stir for 30 min to form a cross-linking system; add the second modified acrylate copolymer dispersion to the cross-linking system, heat to 85°C, and stir at 200 r / min to react for 5 h; coat the reaction liquid on a polyimide substrate with a wet film thickness of 25 μm, pre-bake at 90°C for 1 h, then heat to 130°C and cure for 4 h to obtain a modified acrylate copolymer.

[0034] Example 7, preparation of modified acrylate copolymer, the specific preparation steps are as follows: B1. Add 190 ml of toluene to a four-necked flask, raise the temperature to 90° C., introduce nitrogen protection, then dissolve 45 g of ethyl acrylate, 30 g of butyl methacrylate, and 20 g of 4-hydroxyphenyl trifluoromethylacrylate in 90 ml of toluene to form a monomer solution, and dissolve 2 g of benzoyl peroxide in 90 ml of toluene to form an initiator solution; first, add 1 / 4 of the monomer solution and 1 / 2 of the initiator solution dropwise to the four-necked flask for 40 min, and continue the constant temperature reaction for 1.5 h. Then, add the remaining monomer solution dropwise in three equal parts, each with an interval of 1 h. After each dropwise addition, add 1 / 4 of the total amount of initiator solution. After the dropwise addition is complete, raise the temperature to 100° C. and continue the reaction for 5 h. After the reaction, cool to room temperature, add petroleum ether for precipitation, collect the polymer by filtration, wash with petroleum ether three times, and vacuum dry at 85° C. for 7 h to obtain a first modified acrylate copolymer; B2, take 15g of nano zinc oxide, add 120ml of ethanol, ultrasonically disperse for 35min at 400W power, add 5ml of silane coupling agent KH-570, and stir at 60°C for 3h to obtain a nano zinc oxide dispersion; dissolve 120g of the first modified acrylate copolymer in 240ml of butyl acetate, heat to 80°C, stir at 300r / min speed until completely dissolved, slowly add the nano zinc oxide dispersion, stir with 400W power ultrasound for 50min, then add 3g of polyethylene glycol, continue stirring for 3h, and cool to room temperature to obtain a second modified acrylate copolymer; B3. Dissolve 22g of bisphenol A epoxy acrylate and 1.8g of di-tert-butyl peroxide in 100ml of ethyl acetate and stir for 40min to form a cross-linking system; add the second modified acrylate copolymer dispersion to the cross-linking system, heat to 95°C, and stir at 250r / min for 6h; coat the reaction liquid on a polyimide substrate with a wet film thickness of 35μm, pre-bake at 100°C for 2h, then heat to 140°C and cure for 5h to obtain a modified acrylate copolymer.

[0035] Comparative Example 1: A masking protective tape for semiconductor integrated circuit packaging was prepared. The specific preparation steps are as follows: The remaining steps remain unchanged, except that the nano-silica in Example 3 is replaced by the modified nano-silica prepared in Example 4, to prepare a masking protective tape for semiconductor integrated circuit packaging.

[0036] Comparative Example 2: A masking protective tape for semiconductor integrated circuit packaging was prepared. The specific preparation steps are as follows: The remaining steps remained unchanged, except that the acrylate copolymer in Example 3 was replaced by the modified acrylate copolymer prepared in Example 7 to prepare a masking protective tape for semiconductor integrated circuit packaging.

[0037] Comparative Example 3: A masking protective tape for semiconductor integrated circuit packaging was prepared. The specific preparation steps are as follows: The remaining steps remained unchanged, except that the nano-silica in Example 3 was replaced by the modified nano-silica prepared in Example 4, and the acrylate copolymer was replaced by the modified acrylate copolymer prepared in Example 7, to prepare a masking protective tape for semiconductor integrated circuit packaging.

[0038] Performance Testing ; Performance test results show that Example 3 generally outperforms Examples 1 and 2. Comparative Example 1, which replaces only the modified nano-silica, and Comparative Example 2, which replaces only the modified acrylate copolymer, also outperform the examples. Comparative Example 3, which replaces both modified materials, achieves the highest performance. Specifically, Comparative Example 3 achieves Grade 0 adhesion, a high-temperature adhesive residue rate of only 0.8%, a UV aging yellowing index of 2.1, a tensile strength of 51 MPa, an elongation at break of 300%, a V-0 flame retardancy rating, and isopropyl alcohol resistance with no swelling or whitening. Overall, this demonstrates that the synergistic use of modified nano-silica and modified acrylate copolymer significantly enhances various key properties of the tape.

[0039] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the described specific embodiments or replace them in similar ways. As long as they do not deviate from the invention or exceed the scope defined by the claims, they should all fall within the scope of protection of the present invention.

Claims

1. A masking and protective tape for semiconductor integrated circuit packaging, characterized in that: The masking protective tape for semiconductor integrated circuit packaging is prepared by using polyimide as a base material and coating with a coating. The coating contains the following raw materials in parts by weight: 3-5 parts of modified nano-silicon dioxide, 30-40 parts of N,N-dimethylformamide, 25-30 parts of modified acrylic ester copolymer, 17-26 parts of ethyl acetate, 12-15 parts of epoxy resin, 1-2 parts of silane coupling agent KH-550, 0.5-1 part of antioxidant 1010, 0.3-0.8 part of ultraviolet absorber UV-327, 1-2 parts of carboxyl-terminated nitrile rubber, 2-4 parts of decabromodiphenyl ether, 0.1-0.3 parts of organic silicone defoaming agent, 0.2-0.5 parts of acrylic ester leveling agent, and 10-11 parts of diaminodiphenyl sulfone.

2. The masking and protective tape for semiconductor integrated circuit packaging according to claim 1, wherein: The number average molecular weight of the carboxyl-terminated nitrile rubber is 3000-5000, and the acrylonitrile content is 28%-32%. The carboxyl-terminated nitrile rubber needs to be dried before use. The carboxyl-terminated nitrile rubber is placed in a vacuum drying oven and dried for 3-4 hours at 70-80°C and a vacuum degree of -0.08 to -0.09 MPa to ensure that the moisture content is reduced to below 0.5%. After drying, it is sealed and stored.

3. The masking and protective tape for semiconductor integrated circuit packaging according to claim 1, wherein: The diaminodiphenyl sulfone needs to be ground and screened, and is ground using a planetary ball mill. The grinding medium is agate balls, the ball-to-material ratio is 8:1, the grinding speed is 350 r / min, and the grinding time is 2.5 hours. After grinding, it is sieved through a 400-mesh sieve, and the sieve residue is collected as the diaminodiphenyl sulfone for final use. The sieved diaminodiphenyl sulfone needs to be stored in a dry environment with a relative humidity of ≤40% to avoid uneven cross-linking reaction due to particle agglomeration.

4. The masking and protective tape for semiconductor integrated circuit packaging according to claim 1, wherein: The modified nano-silica is specifically prepared in the following steps: A1. Add 15% by mass hydrochloric acid solution to nano-silica, heat to 60-70°C, and stir at 250-300 r / min for 4-5 hours; filter after reaction, wash with deionized water until neutral, add 8% by mass sodium hydroxide solution, heat to 50-60°C, and stir for 3-4 hours; filter again and wash repeatedly with deionized water until neutral, add deionized water, and ultrasonically disperse at 500 W for 30-40 minutes, add 30% by mass hydrogen peroxide, stir at 40-50°C for 2-3 hours, and finally vacuum dry at 90-100°C for 6-7 hours to obtain the first modified nano-silica; A2. Dissolve acrylamide and methyl methacrylate in an ethanol-water solution with a volume ratio of 3:1, then add azobisisobutyronitrile and stir to dissolve to form a monomer solution; add the first modified nano-silica to the monomer solution, ultrasonically disperse for 20-30 minutes, heat to 70-80°C, introduce nitrogen protection, and stir at 200-250 r / min for 6-8 hours; after the reaction, centrifuge for 15 minutes, wash with ethanol three times, and vacuum dry at 80-90°C for 5-6 hours to obtain the second modified nano-silica; A3. Dissolve hexamethylene diisocyanate and ethyl orthosilicate in ethyl acetate, then add dibutyltin dilaurate and stir for 20-30 minutes to form a crosslinker solution; add the second modified nano-silica to the crosslinker solution, heat to 50-60°C, and stir at 180-220 r / min for 4-5 hours; after the reaction, filter, wash with ethyl acetate three times, and vacuum cure at 100-110°C for 3-4 hours to obtain modified nano-silica.

5. The masking and protective tape for semiconductor integrated circuit packaging according to claim 4, wherein: The usage ratio of nano-silica, hydrochloric acid solution, sodium hydroxide solution, deionized water and hydrogen peroxide in A1 is 350-400g:900-1000ml:800-900ml:500-600ml:5-8ml; The usage ratio of acrylamide, methyl methacrylate, ethanol-water solution, azobisisobutyronitrile, and first modified nano-silica in A2 is 15-20 g: 12-16 g: 400-500 ml: 0.8-1.2 g: 280-320 g; The usage ratio of hexamethylene diisocyanate, ethyl orthosilicate, ethyl acetate, dibutyltin dilaurate, and second modified nano-silica in A3 is 8-12g: 10-14g: 200-250ml: 0.3-0.5g: 200-240g.

6. The masking and protective tape for semiconductor integrated circuit packaging according to claim 1, wherein: The modified acrylate copolymer is specifically prepared in the following steps: B1. Add 160-190 ml of toluene to a four-necked flask, raise the temperature to 85-90° C., and introduce nitrogen protection; dissolve ethyl acrylate, butyl methacrylate, and 4-hydroxyphenyl trifluoromethylacrylate in toluene to form a monomer solution, and dissolve benzoyl peroxide in toluene to form an initiator solution; first, add 1 / 4 of the monomer solution and 1 / 2 of the initiator solution dropwise to the four-necked flask for 30-40 minutes, and continue the reaction at a constant temperature for 1-1.5 hours. Then, add the remaining monomer solution dropwise in three equal parts, each with an interval of 1 hour. After each dropwise addition, add 1 / 4 of the total initiator solution. After the dropwise addition is complete, raise the temperature to 95-100° C. and continue the reaction for 4-5 hours; after the reaction, cool to room temperature, add petroleum ether for precipitation, collect the polymer by filtration, wash with petroleum ether three times, and vacuum dry at 75-85° C. for 6-7 hours to obtain a first modified acrylate copolymer; B2. Add nano-zinc oxide to ethanol, disperse under ultrasonication at 400 W power for 25-35 min, add silane coupling agent KH-570, and stir at 50-60 ° C for 2-3 h to obtain a nano-zinc oxide dispersion; dissolve the first modified acrylate copolymer in butyl acetate, heat to 70-80 ° C, and stir at 250-300 r / min until completely dissolved, slowly add the nano-zinc oxide dispersion, stir with ultrasonication at 400 W power for 40-50 min, then add polyethylene glycol, continue stirring for 2-3 h, and cool to room temperature to obtain a second modified acrylate copolymer; B3, dissolving bisphenol A epoxy acrylate and di-tert-butyl peroxide in ethyl acetate and stirring for 30-40 minutes to form a cross-linking system; The second modified acrylate copolymer dispersion is added to the cross-linking system, the temperature is raised to 85-95°C, and the reaction is stirred at a speed of 200-250r / min for 5-6h; the reaction liquid is coated on a polyimide substrate with a wet film thickness of 25-35μm, pre-baked at 90-100°C for 1-2h, and then heated to 130-140°C and cured for 4-5h to obtain a modified acrylate copolymer.

7. The masking and protective tape for semiconductor integrated circuit packaging according to claim 6, wherein: The ratio of ethyl acrylate, butyl methacrylate, 4-hydroxyphenyl trifluoromethylacrylate, and toluene in the monomer solution of B1 is 40-45 g: 25-30 g: 15-20 g: 70-90 ml; the ratio of benzoyl peroxide and toluene in the initiator solution is 1.5-2 g: 70-90 ml; 160-190 ml of toluene is added to the four-necked flask as the reaction solvent; The usage ratio of nano zinc oxide, ethanol and silane coupling agent KH-570 in the nano zinc oxide dispersion in B2 is 10-15g:100-120ml:3-5ml; the usage ratio of the first modified acrylate copolymer, butyl acetate and polyethylene glycol is 100-120g:200-240ml:2-3g; The usage ratio of bisphenol A epoxy acrylate, di-tert-butyl peroxide and ethyl acetate in the cross-linking system B3 is 18-22 g: 1.2-1.8 g: 80-100 ml.

8. A method for preparing a masking protective tape for semiconductor integrated circuit packaging, characterized in that: The specific steps include: S1. Dissolving the modified nano-silica in N,N-dimethylformamide and ultrasonically dispersing for 30 minutes to prepare a modified nano-silica dispersion; dissolving the modified acrylate copolymer in ethyl acetate and stirring until completely dissolved to prepare a modified acrylate copolymer solution; S2. Add N,N-dimethylformamide to the reactor, stir at 300-400 r / min and heat to 40-45°C, add the modified acrylate copolymer solution, and stir for 15-20 minutes until uniform; then add the epoxy resin, heat to 50-55°C, increase the speed to 500-600 r / min, and stir for 30-40 minutes to form a mixed resin system; S3. First add silane coupling agent KH-550 to the mixed resin and stir for 10-15 minutes, then add modified nano-silica dispersion, ultrasonically disperse at 500W for 30-40 minutes and maintain stirring at 400-500r / min; add antioxidant 1010, UV absorber UV-327, carboxyl-terminated nitrile rubber, and decabromodiphenyl ether in sequence, stirring each for 20-25 minutes; finally add organosiloxane defoamer and acrylate leveling agent, and stir at 200-300r / min for 15-20 minutes; S4. Cool the reactor to 30-35°C, add diaminodiphenyl sulfone and stir for 25-30 minutes, measure the viscosity and adjust it to 8000-12000 mPa·s, adjust the solid content to 48%-52%, filter the prepared coating through three layers of filter cloth with 10 μm, 5 μm and 2 μm, transfer the filtrate into a sealed tank, age at 25-30°C in the dark for 8-10 hours, and stir at 100-150 r / min for 5-10 minutes every 2 hours to prevent precipitation, thereby obtaining the coating; S5. Cut the polyimide substrate into the required size, wipe it with ethanol to remove dust, dry it in a vacuum at 120-130°C for 4-5 hours, and then cool it to 30-40°C. Send it to the coating machine, add the coating into the coating machine storage tank, control the wet film thickness to 30-35μm, and apply it to one side of the substrate at a speed of 0.8-1m / min to avoid orange peel and missing coating on the coating; S6. The coated substrate is pre-baked at 90-100°C for 2-3 hours to remove the solvent, and then cured at 120-130°C for 3.5-4.5 hours to cross-link the coating into a dense layer; after curing, the semi-finished product is cooled to room temperature via a 25°C cooling roller to obtain a masking protective tape for semiconductor integrated circuit packaging.

9. The method for preparing a masking and protective tape for semiconductor integrated circuit packaging according to claim 8, wherein: The solid content of S4 is adjusted by adding N,N-dimethylformamide if it is too high, and stirring and volatilizing at 40° C. if it is too low.

Citation Information

Patent Citations

  • Double side flexible copper coated board and manufacturing method thereof

    CN101420820A

  • Resin composition and cover film prepared from same

    CN116410568A

Cited By

  • Ultraviolet absorption stabilizer and application thereof in environment-friendly high-strength PU (polyurethane) synthetic leather

    CN121021485A

  • Adhesive tape for battery insulation and compounding process thereof

    CN121406250A

  • Preparation method of high-performance polyimide film

    CN121609949A